Does It Pay to be a Bilingual Entrepreneur? The Effect of Language Acquisition on Income Among Latino Entrepreneurs in the United States - Wescott, Geoffrey; Griffith, David (Journal of Comparative International Management)

(untitled) (None, 2010)
While African-American and Asian-American entrepreneurs are the subject of several studies on ethnic entrepreneurship, Latino immigrant entrepreneurs are relatively neglected. Previous research shows that non-immigrant ethnic minorities tend to earn more as employees than as entrepreneurs, but the reverse is true for many immigrants. Despite the fact that immigrants from Latin American to the United States have shown a propensity to become self-employed and hold skills that often lead to success in the entrepreneurial market, their income as entrepreneurs is lower than other ethnic groups. This study shows that most of this disparity is linked to languagability. If they are bilingual in Spanish and English with strong English skills, Latino immigrants to America, like other immigrant groups, earn more on average as entrepreneurs than as employees.